Ecosystem destruction and disaster risk incubation– A case of wetland loss and flood disasters in Makurdi town of Nigeria - Stephen, Hemba; Wali, Elekwachi; Hycienth, Ogunka Nwankwoala; Emelu , Victoria (Central Asian Journal of Environmental Science and Technology Innovation, 2020)
Disaster risk is incubated through a series of events that shape and reshape hazards and vulnerability. The gradual destruction of a diversity of ecosystems leading to the depletion of ecosystem services is an incubation period for many disasters as the case of Makurdi wetlands and flood disasters. Makurdi wetlands have been destroyed with only a few remaining according to a recent thirty-year study. This suggests the loss of essential ecosystem services that they provide, including defense against surging floodwaters. In the corresponding period, increased flood disaster incidences have been reported in Makurdi, with a corresponding increase in size and intensity of devastating impact on the populations. Surprisingly surveys carried out in Makurdi on the causes of flood demonstrate a minimal knowledge of the significance of wetlands in managing flood disasters. The ability of ecosystems to continue to provide ecosystem services requires deliberate management action through sustainable practices, knowledge, and attitudes of people who live near or within such ecosystems and who draw such services from there. This paper reviews and points to the risk incubation effect of a long period of continuous wetland destruction in Makurdi. It draws scientific interest to the conservation of Makurdi wetlands and answers questions on the importance of wetlands in flood disasters prevention, management, and recovery in Makurdi. It suggests improved wetland management practices and supports the conservation of the remaining Makurdi wetlands.
Keywords: Wetland Ecosystems Disaster Risk Flood Hazards Incubation Conservation